Irreversible Investment, Incremental Capital Accumulation, and Price Uncertainty - Luis H. R. Alvarez (Aboa Centre for Economics (ACE), 2006)
We consider optimal incremental capital accumulation in the presence of investment irreversibility and general price uncertainty. We present a set of general conditions under which the optimal capital accumulation path can be explicitly characterized in terms of an ordinary threshold rule stating that investment is optimal whenever the underlying price exceeds a capital-dependent threshold. We also present a set of general conditions under which increased price volatility expands the region where investment is suboptimal and decreases both the expected cumulative present value of the marginal revenue product of capital and the value of the future expansion options.
Keywords: G31; D92; C61; 330; Price uncertainty; irreversible investment; incremental capital accumulation